Temporal lobe epilepsy in childhood: review article - Franzon,Renata C. (2006)
INTRODUCTION: The authors present a review article on temporal lobe epilepsy in childhood. METHODS: We performed a search in the literature. RESULTS: The main etiologies of temporal lobe epilepsy in childhood are developmental tumors and focal cortical displasia, besides temporal medial sclerosis. The clinical features may be variable particularly in children younger than six years of age. Epilepsy may present with generalized seizures. Electroencephalographic findings are also variable and show a functional dysfunction of several brain areas besides temporal lobes, especially frontal lobes. CONCLUSION: Recent advances demonstrate that temporal lobe epilepsy in childhood present with great etiologic, clinical and electroencephalographic diversity.